Cosolvent-directed diels-alder reaction in ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry A, 2011)
The rate constants of a bimolecular Diels-Alder reaction in binary mixtures of ionic liquids prepared in molecular solvents were analyzed to investigate the effect of viscosity of the medium and solvent effect. In this connection, we have carried out the Diels-Alder reaction of anthracene 9-carbinol with N-ethyl maleimide in binary mixtures of pyridinium-based ionic liquids, 1-butyl-pyridinium tetrafluoroborate, 1-buty1-3-pyridinium tetrafluoroborate, and 1-butyl-4-methyl pyridinium tetrafluoroborate in water, methanol, and chloroform at 298.15 K. The rates of reaction decreased, caused by gradually increasing the volume fraction of ionic liquids in solvents for all three ionic liquids. The kinetic results demonstrate a successful application of the pairwise interaction model built upon the concept of enforced hydrophobic hydration. A temperature-dependent study of kinetics of the Diels-Alder reaction was carried out in the binary mixtures of ionic liquids in water and was explained by the entropy-enthalpy compensation effect based upon activation parameters. Kinetics of the Diels-Alder reaction in highly aqueous medium was noted to be entropically driven.